2016
DOI: 10.1007/s00268-016-3551-9
|View full text |Cite
|
Sign up to set email alerts
|

Actual Long‐Term Survival Outcome of 403 Consecutive Patients with Hilar Cholangiocarcinoma

Abstract: Actual 5-year OS rate after R0 resection of hilar cholangiocarcinoma is 30.1 %. Adjuvant treatment could be beneficial in patients with lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 48 publications
7
54
0
Order By: Relevance
“…Although extended liver resection combined with extrahepatic bile duct resection and systematic dissection of regional lymph nodes have been performed within the last decades, the overall prognosis is still unfavorable. In contrast, several recent studies indicated that adjuvant therapy could improve survival in resected HC, especially for patients with lymph node metastasis and positive surgical margin . Thus, a better understanding of the biological characteristics of HC might help to predict patients’ prognosis and develop a more individualized treatment.…”
Section: Introductionmentioning
confidence: 96%
“…Although extended liver resection combined with extrahepatic bile duct resection and systematic dissection of regional lymph nodes have been performed within the last decades, the overall prognosis is still unfavorable. In contrast, several recent studies indicated that adjuvant therapy could improve survival in resected HC, especially for patients with lymph node metastasis and positive surgical margin . Thus, a better understanding of the biological characteristics of HC might help to predict patients’ prognosis and develop a more individualized treatment.…”
Section: Introductionmentioning
confidence: 96%
“…Relative report is rare in the world up to now. Hilar cholangiocarcinoma has a poor prognosis, especially when it occurs with lymph node metastasis or vessel invasion [5,6]. We recently had a patient who underwent a pure laparoscopic extended right hepatectomy and lymph node dissection and hepaticojejunostomy for a type IIIa hilar cholangiocarcinoma.…”
mentioning
confidence: 99%
“…As CCA features a very unfavorable prognosis even after successful tumor resection [61-63], new strategies are needed to better understand which patients benefit most from extended liver surgery or systemic therapy and which patients should be offered best supportive care. Prognostic circulating biomarkers for CCA that might help to overcome this challenge are reviewed in the following section.…”
Section: Resultsmentioning
confidence: 99%